Civil and environmental systems engineering - ReVelle, Charles (Prentice Hall, 1997)
For junior/senior-level courses in Systems Analysis or Systems Analysis and Economics as applied to civil engineering.Broad and comprehensive in coverage -- and student-friendly in approach -- this text focuses on the most modern skills available for the design, operation and evaluation of civil and environmental engineering systems -- optimization/systems modeling and engineering economics. Exceptionally practical, it features several chapters that present new techniques and methodologies in the context of real-life problem situations.